Bibliometric indicators: spread reflections for a focusing and conscious use - Tessa Piazzini (JLIS.it, 2010)
The usage of bibliometric indicators is widespread in the scientific and academic world, and has become a standard in order to assign research funds and to assess the results of those investments. The aim of this article is to offer, without any claims for comprehensiveness some reflections and advices for using these tools in a more conscious way, highlighting their limits and peculiarities. Apart from Impact Factor, many tools related to Open Access have been developed recently. The most valuable options are given by Scimago, a free tool by the CSIC (Consejo Superior de Investigaciones Científicas), and Eigenfactor, research project of the the University of Washington. The H-Index (or Hirsch Index), developed in 2005 by professor Jorge E. Hirsch at the university of California, offers a valid option to the previous bibliometric analysis tools: the H-Index attempts to reduce some excesses of the Citation Index, making compliant very prolific but low quoted authors, with less prolific and high quoted ones.